Pengaruh Kualitas Sumber Daya Manusia dan Budaya Organisasi terhadap Responsivitas Pelayanan Pelayanan Pegawai di Badan Pusat Statistik Kabupaten Deli Serdang - Kartika, Nona; Supriadi, Supriadi; Julkarnain, Julkarnain (JRMB (Jurnal Riset Manajemen & Bisnis), 2024)
The formulation of the problem is the still high level of complaints submitted by the public regarding services at BPS and to see whether there is an influence of the quality of human resources and organizational culture on the responsiveness of services. The purpose of this study is to analyze and determine the influence of the quality of human resources and organizational culture on the responsiveness of employee services at BPS Deli Serdang Regency. This data analysis technique uses a quantitative approach with a linkert scale, the population in this study were all employees of the Central Statistics Agency of Deli Serdang Regency totaling 148 people and sampling was carried out with a total sampling of 60 respondents. The calculation results in this study used multiple linear regression analysis with the help of SPSS version 27 which is based on the results of the partial test (t test) the value of the influence of HR quality (1.729) t-table (2.002) and the significance value (0.089) sig (0.05) the results of the influence of organizational culture (12.766) t-table (2.002) and the significance value (0.01) sig (0.05) then it can be concluded partially that only organizational culture has a positive and significant effect on the responsiveness of employee services at BPS Deli Serdang Regency. However, based on the simultaneous test (f test), the f-count value (101.967) f-table (3.16) and the significance value obtained (0.01) sig (0.05) So it can be concluded that the quality of human resources (X1) and organizational culture (X2) have met the F test requirements, which means that simultaneously both variables, namely the quality of human resources and organizational culture, have an influence and are significant to the responsiveness of employee services with a determination value of (77.4%).